Sanz Mínguez, C. y Pinto Sanz, J. (eds.) (2024): Pintia. Joyas de vidrio para la eternidad - Mederos Martín, Alfredo (Cuadernos de Prehistoria y Arqueología de la Universidad Autónoma de Madrid, 2025)
reseña